2020
DOI: 10.1302/2633-1462.15.bjo-2020-0027.r1
|View full text |Cite
|
Sign up to set email alerts
|

Personal protective equipment during the COVID-19 crisis: a snapshot and recommendations from the frontline of a university teaching hospital

Abstract: Aims The adequate provision of personal protective equipment (PPE) for healthcare workers has come under considerable scrutiny during the COVID-19 pandemic. This study aimed to evaluate staff awareness of PPE guidance, perceptions of PPE measures, and concerns regarding PPE use while caring for COVID-19 patients. In addition, responses of doctors, nurses, and other healthcare professionals (OHCPs) were compared. Methods The inclusion criteria were all staff working in clinical areas of the hospital. Staff were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 5 publications
2
25
0
Order By: Relevance
“…Similarly, practice closures or reductions have been reported by previous studies [16][17][18][19][20][21][22][23]. Some reports in the literature have demonstrated that most dentists accepted that they were at high risk and were afraid of contracting/spreading the COVID-19 virus to their families [2,18,24,25]. Nevertheless, in this study, 75% of all pediatric dentists continued to live with their families during the COVID-19 lockdown period.…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, practice closures or reductions have been reported by previous studies [16][17][18][19][20][21][22][23]. Some reports in the literature have demonstrated that most dentists accepted that they were at high risk and were afraid of contracting/spreading the COVID-19 virus to their families [2,18,24,25]. Nevertheless, in this study, 75% of all pediatric dentists continued to live with their families during the COVID-19 lockdown period.…”
Section: Discussionsupporting
confidence: 72%
“…All patients were assessed with "Amber (inpatient contact – non-AGP)" protective equipment precautions ( Figure 1 ). 6 , 10 , 11 All patients requiring follow-up or possible operative intervention were discussed with the on-call orthopaedic consultant based in the MIU. Out-of-hours patients were discussed in the following morning trauma meeting.…”
Section: Methodsmentioning
confidence: 99%
“…Within the hood of health psychology, various behavioral theories exist. These theories underline the role of persuasive socio-psychological constructs while conceptualizing health-concerned behavior of individuals, e.g., conceptualizing the health-protective behavior of the workforce ( Barello et al, 2020 ; Mathai, 2020 ; Almazyad et al, 2021 ) or being vaccinated to avoid serious health crisis ( Hu et al, 2017 ; Zampetakis and Melas, 2021 ). In each scenario, most of the health-protective theories underline the constructs that can help mitigate the health challenges or adopt measures to avoid health challenges (i.e., pandemic crisis).…”
Section: Theoretical Backgroundmentioning
confidence: 99%